Supporting Future Career Of Autistic Learners Via Technology: Design And Development Of iBakery Courseware - Shahbodin, Faaizah; Maria, Meylinda; Che Ku Mohd, Che Ku Nuraini; Jaafar, Nurul Amiera (Penerbit UTHM, 2019)
The evolution of education affects the style and approach of teaching and learning. Education 4.0 as the current evolution in education focuseson the students and the usage of technology. iBakery as a form of iBook is one of the technology implementationsin education for Autistic students. iBakery is an Autistic user-friendlycourseware which provides a set of instructions needed in bakingactivity. By concentrating on theinterface, content presentation, and flow of the system, iBakery could help Autistic students to learn about bakery in a fun way. From the qualitative testing which has beenconducted towards target users, results show positive feedbacks on iBakery from both teachers and Autistic students. It is believed that iBakery could help Autistic students to gain theirbaking skills which could be applied in their future life as a chance of independent living and career opportunity